1981
DOI: 10.1007/bf01320794
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between plaque size and the immunising ability of the foot-and-mouth disease virus SAT1 Nig 10/75

Abstract: Qualitative and quantitative laboratory tests on small and large plaque variants of the foot-and-mouth disease virus type SAT1Nig10/75 revealed an antigenic similarity which was confirmed by vaccine potency tests in guinea pigs. $ Virus preparations used for vaccines have often been shown to be heterogeneous in terms of the size of plaque they can elicit when plated on to cell monolayers. Where such plaque variants have been found to be stable, they have in many cases been linked with other changes in the viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Previous studies also observed that several viruses and their mutant viruses could form different plaque sizes but present similar virus replication profiles (27, 37). For FMDV, it has been suggested that the plaque phenotype is not necessarily of significance for production of FMDV vaccine antigen (38). Here, our data also showed that the ability of rO-WT and rO-DPKs86 to form large or small plaques did not correlate with the ability of the viruses to replicate in BHK-21, PK-15, and BTY cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also observed that several viruses and their mutant viruses could form different plaque sizes but present similar virus replication profiles (27, 37). For FMDV, it has been suggested that the plaque phenotype is not necessarily of significance for production of FMDV vaccine antigen (38). Here, our data also showed that the ability of rO-WT and rO-DPKs86 to form large or small plaques did not correlate with the ability of the viruses to replicate in BHK-21, PK-15, and BTY cells.…”
Section: Discussionmentioning
confidence: 99%